THE HISTORICAL LANDMARKS OF THE SCHOOL THEATER IN ROMANIA - Ion ALEXANDRESCU (Acta et Commentationes, Sciences of Education, 2020)
In this article we consider the identification and evolution of the National School Theater (TȘ) through the description and comparative analysis of the relevant historiographic research, dedicated to the history of professional theater in the Romanian area. The foundation of the research is related to representative works in several, which offers a lot of information that can be interpreted and used directly and indirectly from the perspective of the advanced theme. Also in this perspective, we intend to research and follow in Mihai Eminescu's footsteps in his pilgrimages along with the great theatrical bands of the time and his role in TȘ. We discover the one who would become the most important poet of the Romanians, in "the great transformation of the nineteenth century " (Massoff Ioan, quoted works). He is fighting for an educational and moralizing theater. He passionately supported the TȘ tradition as a pedagogue and promoted the formative value and impact on the development of the child's personality.